American literature and American identity : a cognitive cultural study from the Revolution through the Civil War - Hogan, Patrick Colm. (New York, NY : Routledge, 2020)
"American Literature and American Identity addresses the crucial issue of identity formation, especially national identity, in influential works of American literature. Patrick Colm Hogan uses techniques of cognitive and affective science to examine the complex and often highly ambivalent treatment of American identity in works by Melville, Cooper, Sedgwick, Apess, Stowe, Jacobs, Douglass, Hawthorne, Poe, and Judith Sargeant Murray. Hogan focuses on the issue of how authors imagined American identity-specifically, as universal, democratic egalitarianism-in the face of the nation's clear and often brutal inequalities of race and sex. In the course of this study, Hogan advances our understanding of nationalism in general, American identity in particular, and the widely read literary works he examines"--
A Note on Usage -- Introduction: The Complex Ambivalence of Being Us -- Chapter One: What is Identity? And What is American? -- Chapter Two: The Last of the Mohicans: Senility and Love in a New Nation -- Chapter Three: Hope Leslie: Critique, Defiance, and Ambivalence -- Chapter Four: William Apess: A Native American Writes Back -- Chapter Five: Uncle Tom's Cabin: The Childhood Model and Delegitimating U.S. Nationalism -- Chapter Six: Harriet Jacobs, Women's Friendship, and Anti-Nationalism -- Chapter Seven: Frederick Douglass, Manhood, and the Lost Home -- Chapter Eight: The Scarlet Letter: Sexuality, Sin, and Spiritual Realization -- Chapter Nine: Poe's "The Black Cat": An Allegory of Misogyny -- Chapter Ten: Judith Sargent Murray on Women's Virtue and the Equality of the Sexes -- Chapter Eleven: Moby Dick: Interracial Romance Beyond the Nation -- Afterword: In Place of a Premature Conclusion.
OCLC-licensed vendor bibliographic record.
Keywords: American literature -- History and criticism; National characteristics, American, in literature; Identity (Psychology) in literature; Race in literature; Equality in literature; Culture in literature; Ambivalence in literature; Literature and society -- United States; LITERARY CRITICISM / American / General